2017
DOI: 10.1038/s41598-017-08380-5
|View full text |Cite
|
Sign up to set email alerts
|

Nosema ceranae, Fipronil and their combination compromise honey bee reproduction via changes in male physiology

Abstract: The honey bee is threatened by biological agents and pesticides that can act in combination to induce synergistic effects on its physiology and lifespan. The synergistic effects of a parasite/pesticide combination have been demonstrated on workers and queens, but no studies have been performed on drones despite their essential contribution to colony sustainability by providing semen diversity and quality. The effects of the Nosema ceranae/fipronil combination on the life traits and physiology of mature drones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 93 publications
2
17
2
1
Order By: Relevance
“…Similar results were obtained for drones reared in laboratory conditions following exposure to fipronil in the sugar syrup, which experienced significantly lower sperm viability and concentration (Kairo et al 2017a). Interestingly, the same research group found that fipronil interacts with the microsporidian parasite Nosema ceranae and their interaction causes lower drone sperm viability and antioxidant activity compared to untreated drones (Kairo et al 2017b).…”
Section: Effects Of Farmer-applied Insecticidessupporting
confidence: 69%
“…Similar results were obtained for drones reared in laboratory conditions following exposure to fipronil in the sugar syrup, which experienced significantly lower sperm viability and concentration (Kairo et al 2017a). Interestingly, the same research group found that fipronil interacts with the microsporidian parasite Nosema ceranae and their interaction causes lower drone sperm viability and antioxidant activity compared to untreated drones (Kairo et al 2017b).…”
Section: Effects Of Farmer-applied Insecticidessupporting
confidence: 69%
“…Second, residual wasp bait that is not taken by pest wasps becomes a dry solid within 3 days and is removed from the bait stations after 3–8 days without replacement. Consequently, the environmental exposure of bee colonies to the toxicant (or its environmental or metabolic breakdown products) and the period over which they could develop sub-lethal effects is shorter than indicated by published toxicity tests [ 36 , 40 , 52 53 ], although even brief periods of exposure can result in subtle sub-lethal effects with both immediate and delayed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Drones are also affected by pesticides. Sublethal concentrations of neonicotinoids and phenylpyrazoles can reduce sperm viability (Kairo et al, 2016(Kairo et al, , 2017aStraub et al, 2016), which can hamper fertilization of queens and the production of diploid workers. Together, reduced sperm transfer and fertilization may limit the production of a genetically diverse workforce, which may compromise the division of labour (Jones et al, 2004) and response to disease (Sherman et al, 1988).…”
Section: Pesticides Can Obstruct Reproduction and Developmentmentioning
confidence: 99%